IL-13 R130Q, a common variant associated with allergy and asthma, enhances effector mechanisms essential for human allergic inflammation - Vladich, Frank D. (American Society for Clinical Investigation, 2005)
Genetic factors are known to strongly influence susceptibility to allergic inflammation. The Th2 cytokine IL-13 is a central mediator of allergy and asthma, and common single-nucleotide polymorphisms in IL13 are associated with allergic phenotypes in several ethnically diverse populations. In particular, IL13+2044G→A is expected to result in the nonconservative replacement of arginine 130 (R130) with glutamine (Q). We examined the impact of IL13+2044G→A on the functional properties of IL-13 by directly comparing the activity of WT IL-13 and IL-13 R130Q on primary human cells involved in the effector mechanisms of allergic inflammation. Our results show that IL-13 R130Q was significantly more active than WT IL-13 in inducing STAT6 phosphorylation and CD23 expression in monocytes and hydrocortisone-dependent IgE switching in B cells. Notably, IL-13 R130Q was neutralized less effectively than WT IL-13 by an IL-13Rα2 decoy. Decreased neutralization of the minor variant could contribute to its enhanced in vivo activity. Neither IL-13 variant was able to engage T cells, which suggests that increased allergic inflammation in carriers of IL13+2044A depends on enhanced IL-13–mediated Th2 effector functions rather than increased Th2 differentiation. Collectively, our data indicate that natural variation in the coding region of IL13 may be an important genetic determinant of susceptibility to allergy.